A5 8 If you liked it, you should have put a Neptune on it - Rai, Jaspreet; Greathead, Edward; Taylor, Josh (Physics Special Topics, 2024)
Neptune experiences pressure sufficient to produce diamonds and this would occur in the layer of Neptune called the icy layer. The distance travelled by the carbon atoms, from the boundary of the atmosphere and the icy layer to form a diamond is found to be 4329 km. The mass of diamonds that could be formed in the entire planet was calculated to be 4.07 × 1023 kg. If this amount of diamond was sold on Earth, it would approximately cost £6.12 × 1030